Three Months of Rifapentine and Isoniazid for Latent Tuberculosis Infection - Sterling, Timothy R; Villarino, M. Elsa; Borisov, Andrey S; Shang, Nong; Gordin, Fred; Bliven-Sizemore, Erin; Hackman, Judith; Hamilton, Carol Dukes; Menzies, Dick; Kerrigan, Amy; Weis, Stephen E; Weiner, Marc; et al. (The New England journal of medicine, 2011)
Treatment of latent TB is an important public-health strategy, but 9 months of daily isoniazid (270 doses) poses challenges for compliance. In this study, 3 months of weekly isoniazid plus rifapentine (12 doses) was found to be noninferior to 9 months of isoniazid alone. Tuberculosis results in nearly 2 million deaths annually worldwide. 1 More than 2 billion persons are infected with Mycobacterium tuberculosis, 2 and from this reservoir active tuberculosis will develop in millions of persons in coming decades. Treatment of latent M. tuberculosis infection among the persons at highest risk for progression to active disease is an important strategy for tuberculosis control and elimination. 3 – 6 The current standard regimen for the treatment of latent M. tuberculosis infection is 9 months of daily isoniazid. 3 The efficacy for isoniazid was found to be 69 to 93% in a study that was published in 1982 (before the . . .